Analisis Dan Perbaikan User Interface/User Experience dengan Metode Double Diamond Pada Website Cv. Bangun Bina Bersaudara - Ekky Febrihandani Rahmawati; Ayuningtyas Ayuningtyas; Tri Sagirani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
A distributor company domiciled in Sidoarjo distributes various kinds of beauty products, gloves and masks, ranging from medical masks to non-medical masks. Currently the promotion is done door to door, causing the assigned salesman to bring a catalog book, product orders are still via WhatsApp. The impact of these problems, resulting in inefficient business processes. The condition of the website owned by the company is less informative and looks very inadequate, the colors on the website are very contrasting and uncomfortable for the eyes, so that the information on the website is not clear and there is a need for improvements to the system flow and user interface. The impact of these problems, resulting in a lack of trust for customers who want to buy products through web companies, because the web display makes customers hesitate in making transactions. To solve this problem, an analysis and improvement of the design appearance was carried out using the double diamond method and the webuse method as a benchmark for perceptions and responses from users. The results of prototype testing get an average value of 0.937 while the results after iterations of prototype testing get an average value of 0.986. Suggestions and criticisms that have been made during the prototype iteration have been accepted by the user.